(untitled) (Journal of Management and Social Sciences, 2016)
Education represents the cornerstone of the society and the major instrument through which it can attain accelerated development. To date, there is not any acceptable measurement of formal education other than examination. It is however unfortunate that this globally embraced yardstick has been abused and compromised through examination malpractice. The main objective of this paper is to emphasize the essence of education in the society, examine the concept of examination malpractice, identify its causes and document its negative effects on the society. Generally, expository methodology was used for the study while historical approach was resorted to where necessary.The paper finds that although there are no categorical Islamic texts on examination malpractice, there are various Qur’anic and Prophetic texts that condemn cheating, deceit, and non-fulfillment of obligations which are manifestations of examination malpractices. Based on the above, the paper suggests God-consciousness, better funding of education and more pro-active participation of parents as measures that would serve as antidote to this educational bane. Â Keywords Examination, malpractices, Islam, Muslim, cheating, morality